Putting on the witch : a retired witches mystery - Lavene, Joyce; Lavene, James (Joyce, Lavene. Retired Witches Mysteries, 2016)
"With their coven's spell book still missing, Molly and Elsie--along with their ghostly friend Olivia, her daughter Dorothy, and her boyfriend Brian--are all on edge, especially now that Dorothy's infamously wicked father is back in the picture. So when they receive an invitation to an exclusive Witches Ball, the ladies jump at the chance to dress up and have some fun. The castle locale is spectacular and the party is hopping, but the festivities come to a swift end when a member of the Grand Council of Witches is murdered. With the whole place on lock down, the coven is determined to find the cunning killer, even with an angry council and a real Spanish Inquisitor breathing down their necks..."--back page of book.